Prevalence of insomnia symptoms and the use of benzodiazepines and Z-drugs for their treatment among medical students - Balčiūnaitė , B.; Būgaitė , V.; Karnickas , M. (Neurologijos seminarai, 2020)
Background. Even though it is common for medical students to complain about insomnia symptoms, no study has been conducted in Lithuania to determine the prevalence of insomnia symptoms among medical students. The aim of this study was to determine the prevalence of insomnia symptoms, to evaluate students’ knowledge about benzodiazepine treatment and to examine the means used by students to treat sleep disorders. Materials and methods. From December 2019 to April 2020, 321 medical students from Vilnius University (VU) (138 students) and Lithuanian University of Health Sciences (LUHS) (183 students) participated in an anonymous online survey including 28 multiple choice questions. The acquired data was analysed using Microsoft Excel and the statistical p value of <0.05 was considered significant. Results. Medical students of all study years participated in the survey (1st year students – 16.8%, 2nd year – 10.9%, 3rd year – 14%, 4th year – 18.4%, 5th year – 22.4%, and 6th year – 17.4%). Of the 321 participants, 262 were female (81.6%) and 59 were male (18.4 %). Over half (55.5%) of all surveyed participants experienced sleep disturbances while studying medicine. The combined prevalence of insomnia symptoms was determined as follows: 56.3% in LUHS and 54.35% in VU; 55.9% prevalence among men and 55.3% prevalence among women. The highest prevalence of insomnia symptoms was recorded in the 1st, 2nd, and 3rd year of medical studies: 28.1%, 26.4% and 22.5%, respectively. Only 45.8% of participants were aware of the recommended duration of treatment with benzodiazepine drugs, which is a maximum of one month. One third (33.9%) of participants, who experienced symptoms of insomnia and used non-pharmacological measures to alleviate those symptoms, also tried using alcohol as a measure to help them fall asleep. Of the participants who experienced symptoms of insomnia (a total of 63 students), 33 (52.4%) used benzodiazepines and 30 (47.3%) used Z-drugs for the treatment. Insomnia symptoms lasting for more than 3 months were experienced by 57 students (17.8% of all participants), while 9 students (2.8% of all participants) experienced insomnia symptoms so severe that they slept less than 2 hours per night. 17 students (5.3% of all participants) experienced symptoms of insomnia 7 days per week. Conclusions. A significantly higher prevalence of insomnia symptoms (55.5%) and a significantly higher prevalence of chronic insomnia symptoms lasting more than 3 months (17.8%) was measured among medical students in comparison to similar studies with non-medical students. Less than half of medical students (45.8%) knew the longest recommended use of benzodiazepines and one in three (33.9%) medical students with symptoms of insomnia also used alcohol as a measure to help them fall asleep.